The effect of meaning in formulating grammatical boundaries The book of al-Muba’ib fi Sharh al-Lama ’by Abu al-Buqa` al-Akbari (d.616 AH) as a model - سلمان جبر سعيد (Journal of College of Education, 2020)
The research deals with the effect of meaning in the formulation of grammatical boundaries in the book of al-Mutab’a fi Sharh al-Lama ’by Abu al-Buqa’ al-Akbari (d.616 AH), by stating the essential semantic expressions in which each grammatical section is completely distinguished from other grammatical topics, especially the topics that share some characteristics, This is because the meaning is of great importance in explaining the grammatical boundaries, and an aim that grammatical studies seek to attain.